Adhesive interactions of N-cadherin limit the recruitment of microtubules to cell-cell contacts through organization of actomyosin - Plestant, Charlotte; Strale, Pierre Olivier; Seddiki, Rima; Nguyen, Emmanuelle; Ladoux, Benoit; Mège, René Marc (Journal of cell science, 2014)
Adhesive interactions of cadherins induce crosstalk between adhesion complexes and the actin cytoskeleton, allowing strengthening of adhesions and cytoskeletal organization. The underlying mechanisms are not completely understood, and microtubules (MTs) might be involved, as for integrin-mediated cell-extracellular-matrix adhesions. Therefore, we investigated the relationship between N-cadherin and MTs by analyzing the influence of N-cadherin engagement on MT distribution and dynamics. MTs progressed less, with a lower elongation rate, towards cadherin adhesions than towards focal adhesions. Increased actin treadmilling and the presence of an actomyosin contractile belt, suggested that actin relays inhibitory signals from cadherin adhesions to MTs. The reduced rate of MT elongation, associated with reduced recruitment of end-binding (EB) proteins to plus ends, was alleviated by expression of truncated N-cadherin, but was only moderately affected when actomyosin was disrupted. By contrast, destabilizing actomyosin fibers allowed MTs to enter the adhesion area, suggesting that tangential actin bundles impede MT growth independently of MT dynamics. Blocking MT penetration into the adhesion area strengthened cadherin adhesions. Taken together, these results establish a crosstalk between N-cadherin, F-actin and MTs. The opposing effects of cadherin and integrin engagement on actin organization and MT distribution might induce bias of the MT network during cell polarization. © 2014. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Actin cytoskeleton; Actin treadmilling; Actomyosin; Adherens junctions; Cell polarization; Microtubule dynamics